PENGARUH LATIHAN SPLIT TERHADAP EKSTENSI TUNGKAI PADA ATLET KARATE KUMITE PEMULA DOJO SD NEGERI 03 MINAS - Cindy Mustika Putri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the observations of researchers at the Dojo of SD Negeri 03 Minas and the results of interviews with coach Ardilah, where the beginner athletes of the Karate Dojo at SD Negeri 03 Minas, have shortcomings which are influenced by one of the factors of physical condition, namely the flexibility (flexibility) where the tone when carrying out the attack is flexibility of the legs. still lacking so that the opponent can anticipate by parrying his attacks and cannot earn points. The title that the researchers examined was "The effect of split training on leg extension in the novice athletes of Karate Dojo SD Negeri Minas so that the purpose of this study was to determine the effect of split training on leg extension in the novice athletes of Karate Dojo SD Negeri 03 Minas. The form of this research is (one group pretest-posttest design) with a population of 10 athletes. The instrument used in this study is to use split exercises which aim to determine how flexible the athlete's foot is. The results obtained were analyzed using the t-test which resulted in a tcount of 5.747 with a ttable of 1.833, Ha was accepted at the alpha level (ɑ) 0.05. It can be concluded that there is an effect of split training on leg extension in the novice athletes of Karate Dojo SD Negeri 03 Minas.Key Words: Split Exercise, Leg Extension, Karate Athletes